Skip to content

Advertisement

  • Research
  • Open Access

Positive solutions to boundary value problems of fractional difference equation with nonlocal conditions

Advances in Difference Equations20142014:7

https://doi.org/10.1186/1687-1847-2014-7

  • Received: 29 July 2013
  • Accepted: 11 December 2013
  • Published:

Abstract

In this paper, we will use the Krasnosel’skii fixed point theorem to investigate a discrete fractional boundary value problem of the form Δ ν y ( t ) = λ h ( t + ν 1 ) f ( y ( t + ν 1 ) ) , y ( ν 2 ) = Ψ ( y ) , y ( ν + b ) = Φ ( y ) , where 1 < ν 2 , t [ 0 , b ] N 0 , f : [ 0 , ) [ 0 , ) is a continuous function, h : [ ν 1 , ν + b 1 ] N ν 1 [ 0 , ) , Ψ , Φ : R b + 3 R are given functionals, where Ψ, Φ are linear functionals, and λ is a positive parameter.

MSC:26A33, 39A05, 39A12.

Keywords

  • nonlocal conditions
  • positive solution
  • cone
  • fixed point theorem

1 Introduction

The theory of fractional differential equations and their applications has received intensive attention. However, the theory of fraction difference equations is still limited. But in the last few years, a number of papers on fractional difference equations have appeared [113]. Among them, Atici and Eloe [1] introduced and developed properties of discrete fractional calculus. In [2], Atici and Eloe studied a two-point boundary valve problem for a finite fractional difference equation. They obtained sufficient conditions for the existence of solutions for the following boundary value problem:
Δ ν y ( t ) = f ( t + ν 1 , y ( t + ν 1 ) ) , y ( ν 2 ) = 0 = y ( ν + b + 1 ) ,
where t [ 0 , b + 1 ] N 0 , 1 < ν 2 , and f : [ ν 1 , ν + b ] N ν 1 × R R is a continuous function. Goodrich [3] deduced uniqueness theorems by means of the Lipschitz condition and deduced the existence of one or more positive solutions by using the cone theoretic techniques for this same boundary value problem. He showed that many of the classical existence and uniqueness theorems for second-order discrete boundary value problems extend to the fraction-order case. In [4], Goodrich obtained the existence of positive solutions to another boundary value problem. Goodrich [5] also considered a pair of discrete fractional boundary value problem of the form
Δ ν 1 y 1 ( t ) = λ 1 a 1 ( t + ν 1 1 ) f 1 ( y 1 ( t + ν 1 1 ) , y 2 ( t + ν 2 1 ) ) , Δ ν 2 y 2 ( t ) = λ 2 a 2 ( t + ν 2 1 ) f 2 ( y 1 ( t + ν 1 1 ) , y 2 ( t + ν 2 1 ) ) y 1 ( ν 1 2 ) = Ψ 1 ( y 1 ) , y 2 ( ν 2 2 ) = Ψ 2 ( y 2 ) , y 1 ( ν 1 + b ) = Φ 1 ( y 1 ) , y 2 ( ν 2 + b ) = Φ 2 ( y 2 ) ,

where t [ 0 , b ] N 0 , λ i > 0 , a i : R [ 0 , ) , ν i ( 1 , 2 ] for each i = 1 , 2 . Ψ i , Φ i : R b + 3 R are given functionals, and f i : [ 0 , ) × [ 0 , ) [ 0 , ) is continuous for each admissible i.

Extensive literature exists on boundary value problems of fractional difference equations [913]. Ferreiraa [9] provided sufficient conditions for the existence and uniqueness of solution to some discrete fractional boundary value problems of order less than 1. Goodrich [1113] studied a ν order ( 1 < ν 2 ) discrete fractional three-point boundary value problem and semipositone discrete fractional boundary value problems.

In this paper, we consider the following boundary value problems of fractional difference equation with nonlocal conditions:
Δ ν y ( t ) = λ h ( t + ν 1 ) f ( y ( t + ν 1 ) ) ,
(1)
y ( ν 2 ) = Ψ ( y ) ,
(2)
y ( ν + b ) = Φ ( y ) ,
(3)

where t [ 0 , b ] N 0 , 1 < ν 2 , f : [ 0 , ) [ 0 , ) is a continuous function. h : [ ν 1 , ν + b 1 ] N ν 1 [ 0 , ) , Ψ , Φ : R b + 3 R are given linear functionals and λ is a positive parameter. The boundary conditions (2)-(3) are generally called nonlocal conditions. Our analysis relies on the Krasnosel’kill fixed-point theorem to get the main results of problem (1)-(3).

The paper will be organized as follows. In Section 2, we will present basic definitions and demonstrate some lemmas in order to prove our main results. In Section 3, we establish some results for the existence of solutions to problem (1)-(3), and we provide an example to illustrate our main results.

2 Preliminaries

Let us first recall some basic lemmas which plays an important role in our discussions.

Definition 2.1 [1]

We define
t ( ν ) = Γ ( t + 1 ) Γ ( t + 1 ν ) ,

for any t and ν for which the right-hand side is defined. We also appeal to the convention that if t + 1 ν is a pole of the Gamma function and t + 1 is not a pole, then t ( ν ) = 0 .

Definition 2.2 [1]

The ν th fractional sum of a function f defined on the set N a : = { a , a + 1 , } , for ν > 0 , is defined to be
Δ ν f ( t ) = Δ ν f ( t ; a ) : = 1 Γ ( ν ) s = a t ν ( t s 1 ) ( ν 1 ) f ( s ) ,
where t { a + ν , a + ν + 1 , } = : N a + ν . We also define the ν th fractional difference, where ν > 0 and 0 N 1 < ν N , to be
Δ ν f ( t ) = Δ N Δ ν N f ( t ) ,

where t N a + ν .

Lemma 2.1 [1]

Let t and ν be any numbers for which t ( ν ) and t ( ν 1 ) are defined. Then
Δ t ( ν ) = ν t ( ν 1 ) .

Lemma 2.2 [1]

Let 0 N 1 < ν N . Then
Δ ν Δ ν y ( t ) = y ( t ) + c 1 t ( ν 1 ) + c 2 t ( ν 2 ) + + c N t ( ν N ) ,

for some c i R , with 1 i N .

Lemma 2.3 [4]

Let 1 < ν 2 , and h : [ ν 1 , ν + b 1 ] N ν 1 R be given. The unique solution of the FBVP
Δ ν y ( t ) = g ( t + ν 1 ) , y ( ν 2 ) = 0 = y ( ν + b )
is given by
y ( t ) = s = 0 b G ( t , s ) g ( s + ν 1 ) ,
where G : [ ν 2 , ν + b ] N ν 2 × [ 0 , b ] N 0 R is defined by
G ( t , s ) = 1 Γ ( ν ) { t ( ν 1 ) ( ν + b s 1 ) ( ν 1 ) ( ν + b ) ( ν 1 ) ( t s 1 ) ( ν 1 ) , 0 s < t ν + 1 b , t ( ν 1 ) ( ν + b s 1 ) ( ν 1 ) ( ν + b ) ( ν 1 ) , 0 t ν + 1 s b .
(4)

Lemma 2.4 [4]

The Green function G ( t , s ) given in Lemma 2.3 satisfies:
  1. (i)

    G ( t , s ) 0 , for each ( t , s ) [ ν 2 , ν + b ] N ν 2 × [ 0 , b ] N 0 ;

     
  2. (ii)

    max t [ ν 2 , ν + b ] N ν 2 G ( t , s ) = G ( s + ν 1 , s ) for each s [ 0 , b ] N 0 ; and

     
  3. (iii)
    there exists a number γ ( 0 , 1 ) such that
    min ν + b 4 t 3 ( ν + b ) 4 G ( t , s ) γ max t [ ν 2 , ν + b ] N ν 2 G ( t , s ) = γ G ( s + ν 1 , s ) ,

    for s [ 0 , b ] N 0 .

     
Theorem 2.1 Let f : [ 0 , ) [ 0 , ) , and Ψ , Φ C ( [ ν 2 , ν + b ] N ν 2 , R ) be given. A function y ( t ) is a solution of the discrete FBVP (1)-(3) if and only if y ( t ) is a fixed point of the operator
T y ( t ) : = α ( t ) Ψ ( y ) + β ( t ) Φ ( y ) + λ s = 0 b G ( t , s ) h ( s + ν 1 ) f ( y ( s + ν 1 ) ) ,
(5)
where
α ( t ) : = 1 Γ ( ν 1 ) [ t ( ν 2 ) 1 b + 2 t ( ν 1 ) ] ,
(6)
β ( t ) : = t ( ν 1 ) ( ν + b ) ( ν 1 ) ,
(7)

and G ( t , s ) is as given in Lemma 2.3.

Proof From Lemma 2.2, we find that a general solution to problem (1)-(3) is
y ( t ) = Δ ν λ h ( t + ν 1 ) f ( y ( t + ν 1 ) ) + c 1 t ( ν 1 ) + c 2 t ( ν 2 ) .
From the boundary condition (2), we get
y ( ν 2 ) = Δ ν λ h ( t + ν 1 ) f ( y ( t + ν 1 ) ) | t = ν 2 + c 1 ( ν 2 ) ( ν 1 ) + c 2 ( ν 2 ) ( ν 2 ) = 1 Γ ( ν ) s = 0 t ν ( t s 1 ) ( ν 1 ) λ h ( s + ν 1 ) f ( y ( s + ν 1 ) ) | t = ν 2 + c 2 Γ ( ν 1 ) = c 2 Γ ( ν 1 ) = Ψ ( y ) ,
so
c 2 = Ψ ( y ) Γ ( ν 1 ) .
On the other hand, applying the boundary condition (3) to y ( t ) implies that
y ( ν + b ) = Δ ν λ h ( t + ν 1 ) f ( y ( t + ν 1 ) ) | t = ν + b + c 1 ( ν + b ) ( ν 1 ) + c 2 ( ν + b ) ( ν 2 ) = 1 Γ ( ν ) s = 0 t ν ( t s 1 ) ( ν 1 ) λ h ( s + ν 1 ) f ( y ( s + ν 1 ) ) | t = ν + b + c 1 ( ν + b ) ( ν 1 ) + Ψ ( y ) Γ ( ν 1 ) ( ν + b ) ( ν 2 ) = Φ ( y ) .
Namely
c 1 ( ν + b ) ( ν 1 ) = Φ ( y ) Ψ ( y ) Γ ( ν 1 ) ( ν + b ) ( ν 2 ) + 1 Γ ( ν ) s = 0 t ν ( t s 1 ) ( ν 1 ) λ h ( s + ν 1 ) f ( y ( s + ν 1 ) ) | t = ν + b ,
so
c 1 = Φ ( y ) ( ν + b ) ( ν 1 ) Ψ ( y ) ( ν + b ) ( ν 2 ) Γ ( ν 1 ) ( ν + b ) ( ν 1 ) + 1 Γ ( ν ) ( ν + b ) ( ν 1 ) s = 0 b ( ν + b s 1 ) ( ν 1 ) λ h ( s + ν 1 ) f ( y ( s + ν 1 ) ) = Φ ( y ) ( ν + b ) ( ν 1 ) Ψ ( y ) ( b + 2 ) Γ ( ν 1 ) + 1 Γ ( ν ) ( ν + b ) ( ν 1 ) s = 0 b ( ν + b s 1 ) ( ν 1 ) λ h ( s + ν 1 ) f ( y ( s + ν 1 ) ) .
Finally, we get
y ( t ) = 1 Γ ( ν ) s = 0 t ν ( t s 1 ) ( ν 1 ) λ h ( s + ν 1 ) f ( y ( s + ν 1 ) ) + ( Φ ( y ) ( ν + b ) ( ν 1 ) Ψ ( y ) ( b + 2 ) Γ ( ν 1 ) ) t ( ν 1 ) + t ( ν 1 ) Γ ( ν ) ( ν + b ) ( ν 1 ) s = 0 b ( ν + b s 1 ) ( ν 1 ) λ h ( s + ν 1 ) f ( y ( s + ν 1 ) ) + Ψ ( y ) Γ ( ν 1 ) t ( ν 2 ) = Ψ ( y ) ( t ( ν 1 ) ( b + 2 ) Γ ( ν 1 ) + t ( ν 2 ) Γ ( ν 1 ) ) + Φ ( y ) t ( ν 1 ) ( ν + b ) ( ν 1 ) + s = 0 t ν ( t ( ν 1 ) ( ν + b s 1 ) ( ν 1 ) Γ ( ν ) ( ν + b ) ( ν 1 ) ( t s 1 ) ( ν 1 ) Γ ( ν ) ) λ h ( s + ν 1 ) f ( y ( s + ν 1 ) ) + s = t ν + 1 b t ( ν 1 ) ( ν + b s 1 ) ( ν 1 ) Γ ( ν ) ( ν + b ) ( ν 1 ) λ h ( s + ν 1 ) f ( y ( s + ν 1 ) ) = Ψ ( y ) α ( t ) + Φ ( y ) β ( t ) + λ s = 0 b G ( t , s ) h ( s + ν 1 ) f ( y ( s + ν 1 ) ) .

Consequently, we see that y ( t ) is a solution of (1)-(3) if and only if y ( t ) is a fixed point of (5), as desired. □

Lemma 2.5 The function α ( t ) is strictly decreasing in t, for t [ ν 2 , ν + b ] N ν 2 . In addition, min t [ ν 2 , ν + b ] N ν 2 α ( t ) = 0 , and max t [ ν 2 , ν + b ] N ν 2 α ( t ) = 1 . On the other hand, the function β ( t ) is strictly increasing in t, for t [ ν 2 , ν + b ] N ν 2 . In addition, min t [ ν 2 , ν + b ] N ν 2 β ( t ) = 0 , and max t [ ν 2 , ν + b ] N ν 2 β ( t ) = 1 .

Proof Note that for every t [ ν 2 , ν + b ] N ν 2 ,
Δ t α ( t ) = Δ t ( t ( ν 2 ) Γ ( ν 1 ) t ( ν 1 ) ( b + 2 ) Γ ( ν 1 ) ) = 1 Γ ( ν 1 ) ( ( ν 2 ) t ( ν 3 ) ( ν 1 ) t ( ν 2 ) b + 2 ) < 0 .
So, the first claim about α ( t ) holds. On the other hand,
α ( ν 2 ) = ( ν 2 ) ( ν 2 ) Γ ( ν 1 ) ( ν 2 ) ( ν 1 ) ( b + 2 ) Γ ( ν 1 ) = 1 , α ( ν + b ) = ( ν + b ) ( ν 2 ) Γ ( ν 1 ) ( ν + b ) ( ν 1 ) ( b + 2 ) Γ ( ν 1 ) α ( ν + b ) = Γ ( ν + b + 1 ) Γ ( ν + b + 1 ν + 2 ) Γ ( ν 1 ) Γ ( ν + b + 1 ) Γ ( ν + b + 1 ν + 1 ) ( b + 2 ) Γ ( ν 1 ) α ( ν + b ) = Γ ( ν + b + 1 ) Γ ( b + 3 ) Γ ( ν 1 ) Γ ( ν + b + 1 ) Γ ( b + 2 ) ( b + 2 ) Γ ( ν 1 ) α ( ν + b ) = 0 .
It follows that
max t [ ν 2 , ν + b ] N ν 2 α ( t ) = 1 , min t [ ν 2 , ν + b ] N ν 2 α ( t ) = 0 .

In a similar way, it may be shown that β ( t ) satisfies the properties given in the statement of this lemma. We omit the details. □

Corollary 2.1 Let I = [ b + ν 4 , 3 ( b + ν ) 4 ] . There are constants M α , M β ( 0 , 1 ) such that min t I α ( t ) = M α α , min t I β ( t ) = M β β , where is the usual maximum norm.

Lemma 2.6 [14]

Let E be a Banach space, and let K E be a cone in E. Assume the bounded sets Ω 1 , Ω 2 are open subsets of E with 0 Ω 1 Ω ¯ 1 Ω 2 , and let
S : K ( Ω ¯ 2 Ω 1 ) K
be a completely continuous operator such that either
  1. (1)

    S u u , u K Ω 1 , S u u , u K Ω 2 ; or

     
  2. (2)

    S u u , u K Ω 1 , S u u , u K Ω 2 .

     

Then S has a fixed point in K ( Ω ¯ 2 Ω 1 ) .

3 Main results

In the sequel, we let
σ : = 2 max t [ ν 2 , ν + b ] N ν 2 s = 0 b G ( t , s ) h ( s + ν 1 ) ,
(8)
τ : = min t [ ν 2 , ν + b ] N ν 2 s = [ b + ν 4 ν + 1 ] [ 3 ( b + ν ) 4 ν + 1 ] G ( t , s ) h ( s + ν 1 ) ,
(9)
γ ˜ : = min { γ , M α , M β } ,
(10)
where γ is the number given in Lemma 2.4(iii). Observe that γ ˜ ( 0 , 1 ) . We now present the conditions on Ψ, Φ, and f that we presume in the sequel:
  • (S1) lim y 0 f ( y ) y = , lim y f ( y ) y = .

  • (S2) lim y 0 f ( y ) y = 0 , lim y f ( y ) y = 0 .

  • (S3) lim y 0 f ( y ) y = l , 0 < l < .

  • (S4) lim y f ( y ) y = L , 0 < L < .

  • (G1) The functionals Ψ, Φ are linear. In particular, we assume that
    Ψ ( y ) = i = ν 2 ν + b c i ν + 2 y ( i ) , Φ ( y ) = k = ν 2 ν + b d k ν + 2 y ( k ) ,

    for c i ν + 2 , d k ν + 2 R .

  • (G2) We have both i = ν 2 ν + b c i ν + 2 G ( i , s ) 0 and k = ν 2 ν + b d k ν + 2 G ( k , s ) 0 , for each s [ 0 , b ] N 0 , and
    i = ν 2 ν + b c i ν + 2 + k = ν 2 ν + b d k ν + 2 1 2 .
  • (G3) Each of Ψ ( α ) , Ψ ( β ) , Φ ( α ) , Φ ( β ) is nonnegative.

First, we let represent all maps from [ ν 2 , ν + b ] N ν 2 into , and equipped with the maximum norm . Clearly, is a Banach space. We define the cone K B by
K : = { y B | y ( t ) 0 , min t [ b + ν 4 , 3 ( ν + b ) 4 ] y ( t ) γ ˜ y , Ψ ( y ) 0 , Φ ( y ) 0 } .
(11)

Lemma 3.1 Assume that (G1)-(G3) hold, and let T be the operator defined in (5). Then T : K K .

Proof For every y K , by (G1), we show first that
Ψ ( T y ) = i = ν 2 ν + b c i ν + 2 ( T y ) ( i ) = i = ν 2 ν + b c i ν + 2 s = 0 b G ( i , s ) λ h ( s + ν 1 ) f ( y ( s + ν 1 ) ) + i = ν 2 ν + b j = ν 2 ν + b c i ν + 2 c j ν + 2 y ( j ) α ( i ) + i = ν 2 ν + b k = ν 2 ν + b c i ν + 2 d k ν + 2 y ( k ) β ( i ) = Ψ ( s = 0 b G ( t , s ) λ h ( s + ν 1 ) f ( y ( s + ν 1 ) ) ) + Ψ ( α ) Ψ ( y ) + Ψ ( β ) Φ ( y ) .
By assumptions (G2) and (G3) together with the nonnegativity of f ( y ) and the fact that y K , we can get Ψ ( T y ) 0 :
Φ ( T y ) = k = ν 2 ν + b d k ν + 2 ( T y ) ( k ) = k = ν 2 ν + b d k ν + 2 s = 0 b G ( k , s ) λ h ( s + ν 1 ) f ( y ( s + ν 1 ) ) + k = ν 2 ν + b l = ν 2 ν + b d k ν + 2 c l ν + 2 y ( l ) α ( k ) + k = ν 2 ν + b i = ν 2 ν + b d k ν + 2 d i ν + 2 y ( i ) β ( k ) = Φ ( s = 0 b G ( t , s ) λ h ( s + ν 1 ) f ( y ( s + ν 1 ) ) ) + Φ ( α ) Ψ ( y ) + Φ ( β ) Φ ( y ) .

It also shows that Φ ( T y ) 0 .

On the other hand, it follows from both Lemma 2.4 and Corollary 2.1 that
min t [ b + ν 4 , 3 ( ν + b ) 4 ] ( T y ) ( t ) min t [ b + ν 4 , 3 ( ν + b ) 4 ] λ s = 0 b G ( t , s ) h ( s + ν 1 ) f ( y ( s + ν 1 ) ) + min t [ b + ν 4 , 3 ( ν + b ) 4 ] α ( t ) Ψ ( y ) + min t [ b + ν 4 , 3 ( ν + b ) 4 ] β ( t ) Φ ( y ) γ ˜ max t [ ν 2 , ν + b ] N ν 2 λ s = 0 b G ( t , s ) h ( s + ν 1 ) f ( y ( s + ν 1 ) ) + M α α Ψ ( y ) + M β β Φ ( y ) γ ˜ max t [ ν 2 , ν + b ] N ν 2 λ s = 0 b G ( t , s ) h ( s + ν 1 ) f ( y ( s + ν 1 ) ) + γ ˜ α Ψ ( y ) + γ ˜ β Φ ( y ) γ ˜ T y .
Hence
min t [ b + ν 4 , 3 ( ν + b ) 4 ] ( T y ) ( t ) γ ˜ T y .
Finally, for every y K ,
( T y ) ( t ) = α ( t ) Ψ ( y ) + β ( t ) Φ ( y ) + λ s = 0 b G ( t , s ) h ( s + ν 1 ) f ( y ( s + ν 1 ) ) 0 .

So, we conclude that T : K K , and the proof is complete. □

Lemma 3.2 Suppose that conditions (G1)-(G3) hold, and there exist two different positive numbers a, b such that
max 0 y a f ( y ) a λ σ ;
(12)
min γ ˜ b y b f ( y ) b λ τ .
(13)

Then, problem (1)-(3) has at least one positive solution y ¯ K such that min { a , b } y ¯ max { a , b } .

Proof Let Ω a : = { y K : y < a } . Then, for any y K Ω a , we have
( T y ) ( t ) = α ( t ) Ψ ( y ) + β ( t ) Φ ( y ) + λ s = 0 b G ( t , s ) h ( s + ν 1 ) f ( y ( s + ν 1 ) ) Ψ ( y ) + Φ ( y ) + λ s = 0 b G ( t , s ) h ( s + ν 1 ) a λ σ i = ν 2 ν + b c i ν + 2 y ( i ) + k = ν 2 ν + b d k ν + 2 y ( k ) + λ σ 2 a λ σ ( i = ν 2 ν + b c i ν + 2 + k = ν 2 ν + b d k ν + 2 ) y + a 2 a 2 + a 2 = y ,

that is, T y y for y Ω a K .

On the other hand, we let Ω b : = { y K : y < b } . For any y K Ω b , we have
( T y ) ( t ) = α ( t ) Ψ ( y ) + β ( t ) Φ ( y ) + λ s = 0 b G ( t , s ) h ( s + ν 1 ) f ( y ( s + ν 1 ) ) λ s = [ b + ν 4 ν + 1 ] [ 3 ( b + ν ) 4 ν + 1 ] G ( t , s ) h ( s + ν 1 ) f ( y ( s + ν 1 ) ) λ s = [ b + ν 4 ν + 1 ] [ 3 ( b + ν ) 4 ν + 1 ] G ( t , s ) h ( s + ν 1 ) b λ τ λ τ b λ τ = y ,

that is, T y y for y K Ω b . By means of Lemma 2.6, there exists y ¯ K such that T y ¯ = y ¯ . □

Theorem 3.1 Suppose that conditions (S1), and (G1)-(G3) hold. Then, for every λ ( 0 , λ ) , problem (1)-(3) has at least two positive solutions, where
λ = 1 σ sup r > 0 r max 0 y r f ( y ) .
(14)
Proof Define function q ( r ) = r σ max 0 y r f ( y ) . In view of the continuity of the function f ( y ) , we have q ( r ) C ( ( 0 , ) , ( 0 , ) ) . From lim y 0 f ( y ) y = , we see that lim r 0 r σ f ( r ) = 0 , that is,
r σ f ( r ) r σ max 0 y r f ( y ) = q ( r ) > 0 ,
so
lim r 0 q ( r ) = 0 .
By lim y f ( y ) y = , we see further that lim r q ( r ) = 0 . Thus, there exists r 0 > 0 such that q ( r 0 ) = max r > 0 q ( r ) = λ . For any λ ( 0 , λ ) , by means of the intermediate value theorem, there exist two points l 1 , l 2 ( 0 < l 1 < r 0 < l 2 < ) such that q ( l 1 ) = q ( l 2 ) = λ . Thus, we have
f ( y ) l 1 λ σ , y [ 0 , l 1 ] ; f ( y ) c 2 λ σ , y [ 0 , l 2 ] .
On the other hand, in view of (S1), we see that there exist d 1 , d 2 ( 0 < d 1 < l 1 < r 0 < l 2 < d 2 < ) such that
f ( y ) y 1 λ γ ˜ τ , y ( 0 , d 1 ] [ d 2 γ ˜ , ) .
That is,
f ( y ) d 1 λ τ , y [ d 1 γ ˜ , d 1 ] ; f ( y ) d 2 λ τ , y [ d 2 γ ˜ , d 2 ] .

An application of Lemma 3.2 leads to two distinct solutions of (1)-(3) which satisfy d 1 y 1 ¯ l 1 , l 2 y 2 ¯ d 2 . □

Theorem 3.2 Suppose (S2) and (G1)-(G3) hold. Then for any λ > λ , equations (1)-(3) have at least two positive solutions. Here
λ = 1 τ inf r > 0 r min γ ˜ r y r f ( y ) .
(15)

The proof is similar to Theorem 3.1 and hence is omitted.

Theorem 3.3 Assume that (S3), (S4) and (G1)-(G3) hold. For each λ satisfying
1 γ ˜ τ L < λ < 1 σ l ,
(16)
or
1 γ ˜ τ l < λ < 1 σ L ,
(17)

equations (1)-(3) have a positive solution.

Proof Suppose (16) holds. Let η > 0 be such that
1 γ ˜ τ ( L η ) λ 1 σ ( l + η ) .
Note that l > 0 . There exists H 1 > 0 such that f ( y ) ( l + η ) y for 0 < y H 1 . So, for y K and y = H 1 , we have
( T y ) ( t ) = α ( t ) Ψ ( y ) + β ( t ) Φ ( y ) + λ s = 0 b G ( t , s ) h ( s + ν 1 ) f ( y ( s + ν 1 ) ) Ψ ( y ) + Φ ( y ) + λ ( l + η ) s = 0 b G ( t , s ) h ( s + ν 1 ) y ( s + ν 1 ) = i = ν 2 ν + b c i ν + 2 y ( i ) + k = ν 2 ν + b d k ν + 2 y ( k ) + λ ( l + η ) s = 0 b G ( t , s ) h ( s + ν 1 ) y ( s + ν 1 ) ( i = ν 2 ν + b c i ν + 2 + k = ν 2 ν + b d k ν + 2 ) y + λ ( l + η ) σ 2 y H 1 2 + H 1 2 = y .

That is, T y y for y K and y = H 1 .

Next, since L > 0 , there exists a H ¯ 2 > 0 such that f ( y ) ( L η ) y for y γ ˜ H ¯ 2 . Let H 2 = max { 2 H 1 , H ¯ 2 } . Then, for y K with y = H 2 ,
( T y ) ( t ) = α ( t ) Ψ ( y ) + β ( t ) Φ ( y ) + λ s = 0 b G ( t , s ) h ( s + ν 1 ) f ( y ( s + ν 1 ) ) λ s = 0 b G ( t , s ) h ( s + ν 1 ) f ( y ( s + ν 1 ) ) λ ( L η ) s = [ b + ν 4 ν + 1 ] [ 3 ( b + ν ) 4 ν + 1 ] G ( t , s ) h ( s + ν 1 ) y ( s + ν 1 ) λ ( L η ) γ ˜ y s = [ b + ν 4 ν + 1 ] [ 3 ( b + ν ) 4 ν + 1 ] G ( t , s ) h ( s + ν 1 ) λ ( L η ) γ ˜ y τ y ,

that is, T y y for y K and y = H 2 .

In view of Lemma 2.6, we see that equations (1)-(3) have a positive solution. The other case is similarly proved. □

Example 3.1 Consider the following boundary value problems:
13 10 y ( t ) = λ ( y 1 2 ( t + 3 10 ) + y 2 ( t + 3 10 ) ) ,
(18)
y ( 7 10 ) = 1 12 y ( 13 10 ) 1 25 y ( 53 10 ) ,
(19)
y ( 213 10 ) = 1 30 y ( 83 10 ) 1 100 y ( 73 10 ) ,
(20)
where b = 20 , ν = 13 10 , and we take
f ( y ) = y 1 2 + y 2 , ψ ( y ) = 1 12 y ( 13 10 ) 1 25 y ( 53 10 ) , ϕ ( y ) = 1 30 y ( 83 10 ) 1 100 y ( 73 10 ) ,

f : [ 0 , + ) × [ 0 , + ) [ 0 , + ) , and y is defined on the time scale { 7 10 , 3 10 , , 213 10 } , f and ψ, ϕ satisfy conditions of Theorem 3.1.

A computation shows that λ 5.33 × 10 3 . Then, for every λ ( 0 , λ ) , problem (18)-(20) has at least two positive solutions.

Declarations

Acknowledgements

The authors are very grateful to the reviewers for their valuable suggestions and useful comments, which led to an improvement of this paper. Project supported by the National Natural Science Foundation of China (Grant No. 11271235) and Shanxi Province (2008011002-1) and Shanxi Datong University Institute (2009-Y-15, 2010-B-01, 2013K5) and the Development Foundation of Higher Education Department of Shanxi Province (20101109, 20111020).

Authors’ Affiliations

(1)
School of Mathematics and Computer Sciences, Shanxi Datong University, Datong, Shanxi, 037009, P.R. China
(2)
Department of Mathematics, Shanxi Normal University, Linfen, Shanxi, 041000, P.R. China

References

  1. Atici FM, Eloe PW: Discrete fractional calculus with the nabla operator. Electron. J. Qual. Theory Differ. Equ. 2009, 3: 1–12. (Spec. Ed. I)MathSciNetView ArticleMATHGoogle Scholar
  2. Atici FM, Eloe PW: Two-point boundary value problems for finite fractional difference equations. J. Differ. Equ. Appl. 2011, 17(4):445–456. 10.1080/10236190903029241MathSciNetView ArticleMATHGoogle Scholar
  3. Goodrich CS: Some new existence results for fractional difference equations. Int. J. Dyn. Syst. Differ. Equ. 2011, 3: 145–162.MathSciNetMATHGoogle Scholar
  4. Goodrich CS: Solutions to a discrete right-focal fractional boundary value problem. Int. J. Differ. Equ. 2010, 5(2):195–216.MathSciNetGoogle Scholar
  5. Goodrich CS: Existence of a positive solution to a system of discrete fractional boundary value problems. Comput. Math. Appl. 2011, 217: 4740–4753. 10.1016/j.amc.2010.11.029MathSciNetView ArticleMATHGoogle Scholar
  6. Goodrich CS: Existence and uniqueness of solutions to a fractional difference equation with nonlocal conditions. Comput. Math. Appl. 2011, 61: 191–202. 10.1016/j.camwa.2010.10.041MathSciNetView ArticleMATHGoogle Scholar
  7. Bastos NRO: Discrete-time fractional variational problems. Signal Process. 2011, 91: 513–524. 10.1016/j.sigpro.2010.05.001View ArticleMATHGoogle Scholar
  8. Benchohra M, Hamani S, Ntouyas SK: Boundary value problems for differential equations with fractional order and nonlocal conditions. Nonlinear Anal. 2009, 71: 2391–2396. 10.1016/j.na.2009.01.073MathSciNetView ArticleMATHGoogle Scholar
  9. Ferreira RAC: Existence and uniqueness of solution to some discrete fractional boundary value problems of order less than one. J. Differ. Equ. Appl. 2013, 19: 712–718. 10.1080/10236198.2012.682577View ArticleMathSciNetMATHGoogle Scholar
  10. Ferreira RAC, Torres DFM: Fractional h -difference equations arising from the calculus of variations. Appl. Anal. Discrete Math. 2011, 5: 110–121. 10.2298/AADM110131002FMathSciNetView ArticleMATHGoogle Scholar
  11. Goodrich CS: On a discrete fractional three-point boundary value problem. J. Differ. Equ. Appl. 2012, 18: 397–415. 10.1080/10236198.2010.503240MathSciNetView ArticleMATHGoogle Scholar
  12. Goodrich CS: On a first-order semipositone discrete fractional boundary value problem. Arch. Math. 2012, 99: 509–518. 10.1007/s00013-012-0463-2MathSciNetView ArticleMATHGoogle Scholar
  13. Goodrich CS: On semipositone discrete fractional boundary value problems with nonlocal boundary conditions. J. Differ. Equ. Appl. 2013, 19: 1758–1780.MathSciNetView ArticleMATHGoogle Scholar
  14. Agarwal R, Meehan M, O’Regan D: Fixed Point Theory and Applications. Cambridge University Press, Cambridge; 2001.View ArticleMATHGoogle Scholar

Copyright

© Kang et al.; licensee Springer. 2014

This article is published under license to BioMed Central Ltd. This is an open access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Advertisement